Transcriptomic Study for Identification of Major Nitrogen Stress Responsive Genes in Australian Bread Wheat Cultivars - Sultana, Nigarin; Islam, Shahidul; Juhasz, Angela; Yang, Rongchang; She, Maoyun; Alhabbar, Zaid; Zhang, Jingjuan; Ma, Wujun (Frontiers in Genetics, 2020)
A high nitrogen use efficiency (NUE) in bread wheat is pivotal to sustain high productivity. Knowledge about the physiological and transcriptomic changes that regulate NUE, in particular how plants cope with N deficiency during flowering and grain filling period is crucial in achieving high NUE. Nitrogen response is differentially manifested in different tissues and shows significant genetic variability. A comparative transcriptome study was carried out using RNA-seq analysis to investigate the effect of nitrogen levels on gene expression at anthesis and 10 DPA in second leaf and grain tissues of three Australian wheat (Triticum aestivum) varieties that were known to have varying NUEs. A total of 12344 DEGs were identified under nitrogen stress where down-regulated DEGs were predominantly associated with carbohydrate metabolic process, photosynthesis, light-harvesting, and defence response while the up-regulated DEGs were associated with nucleotide metabolism, proteolysis, and transmembrane transport under nitrogen stress. Protein-protein interaction and KEGG pathways analysis further revealed that highly interacted down-regulated DEGs were involved in light-harvesting and photosynthesis, and up-regulated DEGs were mostly involved in steroid biosynthesis under nitrogen stress. The common down-regulated genes across the cultivars included photosystem II 10 kDa polypeptide family proteins, plant protein 1589 of uncharacterized protein function etc, whereas common up-regulated genes included glutamate carboxypeptidase 2, PLAC8 family protein, a sulfate transporter. On the other hand, high NUE cultivar Mace responded to nitrogen stress by down-regulation of a stress-related gene annotated as beta-1,3- endoglucanase and pathogenesis-related protein (PR-4, PR-1) and up-regulation of MYB/SANT domain-containing RADIALIS like transcription factors. While the medium NUE cultivar Spitfire and low NUE cultivar Volcani demonstrated strong down-regulation of Photosystem II 10 kDa polypeptide family protein and predominant up-regulation of 11S globulin seed storage protein 2 and protein transport protein Sec61 subunit gamma. In grain tissue most of the DEGs were related to nitrogen metabolism and proteolysis. The DEGs with high abundance in high NUE cultivar can be good candidates to develop nitrogen stress tolerant variety with improved NUE.